Population prevalence of atrial fibrillation and QRS prolongation and mortality in people with suspected heart failure. (25th November 2020) - Friday, J.M; Pellicori, P; Hillen, N; McAllister, D; Kean, S; Wolters, M; Cleland, J.C.F
Abstract: Background: The 12-lead electrocardiogram (ECG) is an essential tool for the diagnosis and management of heart failure (HF). There are few population-based studies on the prevalence and prognostic implications of ECG abnormalities in patients with HF. There are also no robust diagnostic criteria for HF. We explored these issues in a large administrative database. Methods: The National Health Service Greater Glasgow and Clyde Health Board serves a population of ∼1.1 million. We obtained de-identified administrative data, including investigations, diagnosis and prescriptions, linked to hospital admissions and deaths, for anyone with a diagnosis of vascular disease or HF or prescribed loop diuretics (LD) or neuro-endocrine antagonists between 1st January 2012 and 1st April 2018. People were classified into 5 exclusive groups: a) prevalent HF; b) incident (or latent) HF with onset during follow-up; c) people taking LDs but with no diagnosis of HF at any time; d) new prescription of LDs during follow-up but with no diagnosis of HF at any time and d) people to whom none of the above applied. ECGs were classified according to heart rhythm (sinus, AF or flutter or pacemaker/CRT/ICD) and QRS duration <100ms, 100–130ms or >130ms. Follow-up for each group started on 1st of January 2012 (prior to the onset of the classifying event for incident groups). Results: During the observation period, of 316, 350 people included, 158, 421 had a recorded ECG (mean of 3.2 per person with an ECG), including 8, 768 prevalent and 13, 195 incident cases of HF. Of those who never got a diagnosis of heart failure, 11, 508 were receiving and a further 14, 633 were newly prescribed LD during follow-up. There were 110, 317 people who did not fall into the above groups, of whom 51, 089 were aged ≥60 years. A higher proportion of those who were prescribed loop diuretics without a diagnosis of heart failure were women. A similar proportion of those with heart failure and those prescribed diuretics alone had, lung disease and renal dysfunction but patients with heart failure had more ischaemic heart disease, more often had a heart rhythm other than sinus and had longer QRS duration. By three years, 8, 816 people (11%) had died, of whom 2, 919 (33%) had a diagnosis of heart failure and 2, 694 (31%) had been prescribed LD without a diagnosis of HF, together accounting for 64% of all deaths. Patients with a rhythm other than sinus had a worse prognosis in all 5 groups of patients. QRS duration >130ms was associated with a worse prognosis in patients with HF or taking LD. Conclusions: Most people with cardiovascular disease who die will first develop HF or be prescribed a LD (indicating possible undiagnosed HF). Patient characteristics of those prescribed LD suggest that many might have HF with preserved left ventricular ejection fraction (HFpEF). Funding Acknowledgement: Type of funding source: None